Novel composite health assessment risk model for older allogeneic transplant recipients: BMT-CTN 1704 - Mohamed L. Sorror; Wael Saber; Brent Logan; Nancy Geller; Anna Bellach; Jianqun Kou; William Wood; John M. McCarty; Thomas G. Knight; Lyndsey Runaas; Laura Johnston; Jeremy Walston; et al. (Blood Advances)
Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) is potentially curative for older adults with hematologic malignancies. Concerns on nonrelapse mortality (NRM) in older adults limit allo-HCT utilization. We executed a prospective, observational study BMT-CTN 1704 (Blood and Marrow Transplant Clinical Trials Network) enrolling allo-HCT recipients aged ≥60 years from 49 centers in the United States. We analyzed associations between 13 measurements of older adult health and NRM within 1 year to construct a comprehensive health assessment risk model (primary-CHARM) using multivariate Fine-Gray model and grouped penalized variable selection. Two machine learning (ML) models (Cox and pseudo-value boosting) were also explored. Models’ performances were compared using area under the curve (AUC), with bootstrap and cross-validation sampling to correct for optimism, decision curve analysis (DCA), calibration, and Brier scores. Among 1105 patients with median age of 67 (range, 60-82) years who received allo-HCT, NRM was 14.4% and overall survival (OS) 71.7% at 1 year. Factors statistically selected for inclusion in primary-CHARM were higher comorbidity burden, lower albumin, higher C-reactive protein, older age, higher weight-loss percentage, lower patient-reported performance score, and cognitive impairment. Primary-CHARM scores were independently associated with higher NRM (hazard ratio [HR], 2.72; P < .0001) and worse OS (HR, 2.09; P < .0001). Bootstrap bias–corrected AUC for primary-CHARM was 0.591. Comparing primary-CHARM with HCT-comorbidity index and 2 ML-CHARM models, calibration, Brier score, and DCA analysis favored primary-CHARM. Primary-CHARM, with mostly simple and readily available parameters, risk stratifies older adults for allo-HCT. Adopting primary-CHARM in practice may promote broader use of HCT by quantifying risk and enhance the design of strategies to improve outcomes. This trial was registered at www.ClinicalTrials.gov as #NCT03992352.